Preparation method of silver-series high-reflectivity back electrode material
By modifying the copper plate with acid and forming the Ag-Sn nanorod array, the problem of LED electrode materials under sulfide erosion is solved, which improves the light extraction rate of LEDs and reduces the risk of vulcanization.
Patent Information
- Application Number
- CN202411444091.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing LED electrode materials are prone to darkening and discoloration under sulfide erosion, resulting in electrode shedding and resistance failure, which may lead to circuit failure.
The copper plate modified with acid is used as the electrode material substrate, and a negative charge surface is formed by ultrasonic cleaning and microetching treatment, and the seed layer of quaternary ammonium cationic polystyrene microspheres is adsorbed, and the SnCl4 atmosphere heat treatment is performed in the plasma device to form Ag-Sn nanometers Rod array.
It effectively improves the light extraction rate of LEDs, reduces total reflection of light and increases the scattering of light, while reducing the contact between sulfide and silver, and reduces the possibility of vulcanization of electrode materials and LEDs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic materials, and in particular to a method for preparing a silver-based high-reflectivity back electrode material. Background Art
[0002] LED, or semiconductor light emitting diode, is a photoelectric device that uses solid semiconductor chips to emit excess energy through carrier recombination to cause photon emission. It is the technical foundation of the current semiconductor lighting industry. The electrode material of LED is one of the key technologies that determine the performance of LED. The metal electrode in the light emitting diode has low light transmittance, and the light emitted from the quantum well is mainly concentrated under the electrode. Therefore, a large amount of light is absorbed by the electrode and cannot be extracted to the outside of the chip.
[0003] In addition, with the development of industrial society, the sulfur-containing gas in the air is increasing. Coupled with the erosion of various volatile sulfides and other pollutants in the air, the surface of the silver electrode is easily affected by sulfidation and becomes dark and discolored, producing silver sulfide, which causes the electrode to fall off and the resistor to fail, which may lead to circuit failure. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a silver-based high-reflectivity back electrode material to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a silver-based high-reflectivity back electrode material, comprising the following preparation steps: (1) After the pure copper plate is ultrasonically cleaned in alcohol for 5 minutes, it is dried at room temperature for 2 hours, immersed in a micro-etching solution, immersed in 20kHz ultrasonic waves for 20-30 minutes, taken out, and then immersed in a 30-45wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 5-7 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; (2) Pipette the quaternary ammonium cationic polystyrene microsphere aqueous solution onto the surface of the acid-treated copper plate and dry it at 100-150°C for 12 h; (3) Place the copper plate prepared in step (2) in a plasma device, transfer the silver nitrate aqueous solution to the surface of the microspheres by a pipette, fill the gap with the solution, introduce nitrogen at a rate of 100 mL / min, raise the temperature to 400°C, keep the temperature for 1 to 2 hours, then introduce SnCl4 / N2, keep the nitrogen flow rate unchanged, and the flow ratio of SnCl4 to N2 is 1:10 to 100. After introducing for 1 to 2 hours, raise the temperature to 540 to 600°C, keep the temperature for 4 to 5 hours, and naturally cool to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0006] Furthermore, in the micro-etching solution of step (1), the sulfuric acid solution, the hydrochloric acid aqueous solution and the phosphoric acid aqueous solution are mixed in a volume ratio of 20-30:15-20:10-20.
[0007] Furthermore, the volume concentration of the sulfuric acid solution is 10-15%.
[0008] Furthermore, the volume concentration of the hydrochloric acid aqueous solution is 15-20%.
[0009] Furthermore, the volume concentration of the phosphoric acid aqueous solution is 10-15%.
[0010] Furthermore, the particle size of the quaternary ammonium cationic polystyrene microspheres in step (2) is 100-200 nm.
[0011] Furthermore, the concentration of the aqueous solution of quaternary ammonium cationic polystyrene microspheres in step (2) is 0.8-1.5 mg / mL.
[0012] Furthermore, the working conditions of the plasma device in step (3) are: the discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz.
[0013] Furthermore, the concentration of the silver nitrate aqueous solution in step (3) is 10-100 mM.
[0014] Furthermore, the silver-based high-reflectivity back electrode material is used in the bottom packaging structure of high-power LEDs.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention adopts an acid-modified copper plate as an electrode material substrate, the surface of which contains carboxyl and hydroxyl groups and has a certain negative charge, and can absorb positively charged polystyrene microspheres, and then autonomously arranges a polystyrene microsphere seed layer on the surface of the copper plate and fixes it on the surface, which is conducive to the subsequent growth of nanosilver. There are gaps between the polystyrene microspheres, which can absorb and accommodate silver nitrate solution. At the same time, the negative charge of the copper plate can combine with silver ions, so that the generated silver nanorods are effectively fixed on the surface of the copper plate, and then plasma enhanced heating treatment is carried out in a SnCl4 atmosphere. As the solvent is removed, the silver nitrate solution gradually moves toward the nanosilver crystal direction. The silver nanoparticles are combined with the Sn element under the action of plasma and high temperature environment, and diffuse and react with each other under the influence of heat. Under the influence of the polystyrene microsphere seed layer, an Ag-Sn nanorod array is formed. The polystyrene microsphere seed layer can reduce the reaction of the Sn element with the copper sheet. As the reaction time increases, the polystyrene microspheres are vaporized by heat and then removed, leaving gaps, so that the electrode material can reduce the total reflection of light, increase the scattering of light, and effectively improve the light extraction rate of the LED. At the same time, the presence of the Sn element can reduce the contact between sulfide and silver, and reduce the possibility of sulfurization of the electrode material and the LED. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] Example 1; (1) A pure copper plate was ultrasonically cleaned in alcohol for 5 minutes, dried at room temperature for 2 hours, immersed in a micro-etching solution, ultrasonically immersed at 20kHz for 20 minutes, taken out, and then immersed in a 30wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 5 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; the micro-etching solution contained a sulfuric acid solution with a volume concentration of 10%, a hydrochloric acid aqueous solution with a volume concentration of 15%, and a phosphoric acid aqueous solution with a volume concentration of 10% in a volume ratio of 20:15:10; (2) using a pipette, transferring a 0.8 mg / mL aqueous solution of quaternary ammonium cationic polystyrene microspheres to the surface of an acid-treated copper plate, and drying at 100° C. for 12 h; the particle size of the quaternary ammonium cationic polystyrene microspheres is 100 nm; (3) The copper plate prepared in step (2) is placed in a plasma device. The discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz. A 10 mM silver nitrate aqueous solution is transferred to the surface of the microspheres by a pipette, and the solution is filled in the gaps. Nitrogen is introduced at a rate of 100 mL / min, and the temperature is raised to 400°C. After keeping the temperature for 1 hour, SnCl4 / N2 is introduced again. The nitrogen flow rate remains unchanged. The flow ratio of SnCl4 to N2 is 1:10. After 1 hour, the temperature is raised to 540°C, maintained for 4 hours, and then naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0018] Example 2; (1) A pure copper plate was ultrasonically cleaned in alcohol for 5 minutes, dried at room temperature for 2 hours, immersed in a micro-etching solution, ultrasonically immersed at 20kHz for 25 minutes, taken out, and then immersed in a 40wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 6 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; the micro-etching solution contained a sulfuric acid solution with a volume concentration of 12%, a hydrochloric acid aqueous solution with a volume concentration of 18%, and a phosphoric acid aqueous solution with a volume concentration of 12% in a volume ratio of 25:18:15; (2) using a pipette, transferring a 1.1 mg / mL aqueous solution of quaternary ammonium cationic polystyrene microspheres to the surface of an acid-treated copper plate, and drying at 120° C. for 12 h; the particle size of the quaternary ammonium cationic polystyrene microspheres is 150 nm; (3) The copper plate prepared in step (2) is placed in a plasma device. The discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz. A 60 mM silver nitrate aqueous solution is transferred to the surface of the microspheres by a pipette, and the solution is filled in the gaps. Nitrogen is introduced at a rate of 100 mL / min, and the temperature is raised to 400°C. After keeping the temperature for 1.5 hours, SnCl4 / N2 is introduced again. The nitrogen flow rate remains unchanged. The flow ratio of SnCl4 to N2 is 1:50. After 1.5 hours of introduction, the temperature is raised to 580°C, maintained for 4.5 hours, and then naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0019] Example 3; (1) A pure copper plate was ultrasonically cleaned in alcohol for 5 minutes, dried at room temperature for 2 hours, immersed in a micro-etching solution, ultrasonically immersed at 20kHz for 30 minutes, taken out, and then immersed in a 45wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 7 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; the micro-etching solution contained a sulfuric acid solution with a volume concentration of 15%, a hydrochloric acid aqueous solution with a volume concentration of 20%, and a phosphoric acid aqueous solution with a volume concentration of 15% in a volume ratio of 30:20:20; (2) Using a pipette, a 1.5 mg / mL aqueous solution of quaternary ammonium cationic polystyrene microspheres was transferred to the surface of an acid-treated copper plate and dried at 150° C. for 12 h; the particle size of the quaternary ammonium cationic polystyrene microspheres was 200 nm; (3) The copper plate prepared in step (2) is placed in a plasma device. The discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz. A 100 mM silver nitrate aqueous solution is transferred to the surface of the microspheres by a pipette, and the solution is filled in the gaps. Nitrogen is introduced at 100 mL / min, and the temperature is raised to 400°C. After keeping the temperature for 2 hours, SnCl4 / N2 is introduced again. The nitrogen flow rate remains unchanged. The flow ratio of SnCl4 and N2 is 1:10~100. After 2 hours of introduction, the temperature is raised to 600°C, maintained for 5 hours, and naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0020] Comparative Example 1; (1) A quaternary ammonium cationic polystyrene microsphere aqueous solution with a concentration of 1.1 mg / mL was transferred to the surface of a pure copper plate by a pipette and dried at 120° C. for 12 h; the particle size of the quaternary ammonium cationic polystyrene microsphere was 150 nm; (2) The copper plate prepared in step (1) is placed in a plasma device. The discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz. A 60 mM silver nitrate aqueous solution is transferred to the surface of the microspheres by a pipette, and the solution is filled in the gaps. Nitrogen is introduced at a rate of 100 mL / min, and the temperature is raised to 400°C. After keeping the temperature for 1.5 hours, SnCl4 / N2 is introduced. The nitrogen flow rate remains unchanged. The flow ratio of SnCl4 to N2 is 1:50. After 1.5 hours, the temperature is raised to 580°C, kept for 4.5 hours, and then naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0021] Comparative Example 2; (1) A pure copper plate was ultrasonically cleaned in alcohol for 5 minutes, dried at room temperature for 2 hours, immersed in a micro-etching solution, ultrasonically immersed at 20kHz for 25 minutes, taken out, and then immersed in a 40wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 6 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; the micro-etching solution contained a sulfuric acid solution with a volume concentration of 12%, a hydrochloric acid aqueous solution with a volume concentration of 18%, and a phosphoric acid aqueous solution with a volume concentration of 12% in a volume ratio of 25:18:15; (2) Using a pipette, a 1.1 mg / mL polystyrene microsphere aqueous solution was transferred to the surface of an acid-treated copper plate and dried at 120° C. for 12 h; the particle size of the polystyrene microspheres was 150 nm; (3) The copper plate prepared in step (2) is placed in a plasma device. The discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz. A 60 mM silver nitrate aqueous solution is transferred to the surface of the microspheres by a pipette, and the solution is filled in the gaps. Nitrogen is introduced at a rate of 100 mL / min, and the temperature is raised to 400°C. After keeping the temperature for 1.5 hours, SnCl4 / N2 is introduced again. The nitrogen flow rate remains unchanged. The flow ratio of SnCl4 to N2 is 1:50. After 1.5 hours of introduction, the temperature is raised to 580°C, maintained for 4.5 hours, and then naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0022] Comparative Example 3: A pure copper plate was placed in a plasma device with a plasma power supply discharge voltage of 22 kV and a discharge frequency of 13 kHz. A 60 mM silver nitrate aqueous solution was transferred to the surface of the microspheres through a pipette, and the gap was filled with the solution. Nitrogen was introduced at 100 mL / min, the temperature was raised to 400°C, and after keeping the temperature for 1.5 hours, SnCl4 / N2 was introduced again. The nitrogen flow rate remained unchanged, and the flow ratio of SnCl4 and N2 was 1:50. After 1.5 hours of introduction, the temperature was raised to 580°C, maintained for 4.5 hours, and naturally cooled to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0023] Comparative Example 4; (1) A pure copper plate was ultrasonically cleaned in alcohol for 5 minutes, dried at room temperature for 2 hours, immersed in a micro-etching solution, ultrasonically immersed at 20kHz for 25 minutes, taken out, and then immersed in a 40wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 6 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; the micro-etching solution contained a sulfuric acid solution with a volume concentration of 12%, a hydrochloric acid aqueous solution with a volume concentration of 18%, and a phosphoric acid aqueous solution with a volume concentration of 12% in a volume ratio of 25:18:15; (2) using a pipette, transferring a 1.1 mg / mL aqueous solution of quaternary ammonium cationic polystyrene microspheres to the surface of an acid-treated copper plate, and drying at 120° C. for 12 h; the particle size of the quaternary ammonium cationic polystyrene microspheres is 150 nm; (3) Place the copper plate prepared in step (2) in a heating device, transfer a 60 mM silver nitrate aqueous solution to the surface of the microspheres using a pipette, fill the gaps with the solution, introduce nitrogen at a rate of 100 mL / min, raise the temperature to 400°C, keep the temperature for 1.5 h, then introduce SnCl4 / N2, keep the nitrogen flow rate constant, and the flow ratio of SnCl4 to N2 is 1:50. After introducing the nitrogen for 1.5 h, raise the temperature to 580°C, keep the temperature for 4.5 h, and naturally cool to room temperature to obtain a silver-based high-reflectivity back electrode material.
[0024] Comparative Example 5: Using electroplating method, a silver layer and a Sn layer are electroplated on the surface of a pure copper plate in sequence, and then heat treated at 300°C for 30 minutes to obtain an electrode material Effect example Table 1 below shows the room temperature thermal conductivity of the electrode materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5, as well as the test data after the electrodes are stored together with sulfur element for a certain period of time, and the performance analysis results of the light extraction efficiency after the electrode materials are packaged in combination with p-GaN, quantum well, and n-GaN in sequence.
[0025] Table 1
[0026] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention uses an acid-modified copper plate as an electrode material substrate, and its surface contains carboxyl and hydroxyl groups, has a certain negative charge, and can adsorb positively charged polystyrene microspheres, and then autonomously arranges a layer of polystyrene microsphere seed layer on the surface of the copper plate, and fixes it on the surface, which is conducive to the subsequent growth of nanosilver. There are gaps between the polystyrene microspheres, which can adsorb and accommodate silver nitrate solution. At the same time, the negative charge of the copper plate can combine with silver ions, so that the generated silver nanorods are effectively fixed on the surface of the copper plate, and then plasma enhanced heat treatment is carried out in a SnCl4 atmosphere, and the silver nitrate solution is removed along with the solvent. It gradually transforms into nanosilver crystals, and under the combined action of plasma and high temperature environment, nanosilver combines with Sn element, and diffuses and reacts with each other under the influence of heat. Under the influence of polystyrene microsphere seed layer, Ag-Sn nanorod array is formed. The polystyrene microsphere seed layer can reduce the reaction of Sn element with copper sheet. As the reaction time increases, the polystyrene microspheres are vaporized by heat and then removed, leaving gaps, so that the electrode material can reduce the total reflection of light, increase the scattering of light, and effectively improve the light extraction rate of LED. At the same time, the presence of Sn element can reduce the contact between sulfide and silver, and reduce the possibility of sulfurization of electrode material and LED.
[0027] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a silver-based highly reflective back electrode material, characterized in that: The method comprises the following preparation steps: (1) After the pure copper plate is ultrasonically cleaned in alcohol for 5 minutes, it is dried at room temperature for 2 hours, immersed in a micro-etching solution, immersed in 20kHz ultrasonic waves for 20-30 minutes, taken out, and then immersed in a 30-45wt% citric acid aqueous solution, and ultrasonically immersed for 5 hours, taken out, washed with deionized water for 5-7 times, and dried at 60°C for 8 hours to obtain an acid-treated copper plate; (2) Pipette the quaternary ammonium cationic polystyrene microsphere aqueous solution onto the surface of the acid-treated copper plate and dry it at 100-150°C for 12 h; (3) Place the copper plate prepared in step (2) in a plasma device, transfer the silver nitrate aqueous solution to the surface of the microspheres by a pipette, fill the gap with the solution, introduce nitrogen at a rate of 100 mL / min, raise the temperature to 400°C, keep the temperature for 1 to 2 hours, then introduce SnCl4 / N2, keep the nitrogen flow rate unchanged, and the flow ratio of SnCl4 to N2 is 1:10 to 100. After introducing for 1 to 2 hours, raise the temperature to 540 to 600°C, keep the temperature for 4 to 5 hours, and naturally cool to room temperature to obtain a silver-based high-reflectivity back electrode material.
2. The method for preparing a silver-based highly reflective back electrode material according to claim 1, characterized in that: In the micro-etching solution of step (1), sulfuric acid solution, hydrochloric acid aqueous solution and phosphoric acid aqueous solution are mixed in a volume ratio of 20-30:15-20:10-20.
3. The method for preparing a silver-based high-reflectivity back electrode material according to claim 2, characterized in that: The volume concentration of the sulfuric acid solution is 10-15%.
4. The method for preparing a silver-based highly reflective back electrode material according to claim 2, characterized in that: The volume concentration of the hydrochloric acid aqueous solution is 15-20%.
5. The method for preparing a silver-based highly reflective back electrode material according to claim 2, characterized in that: The volume concentration of the phosphoric acid aqueous solution is 10-15%.
6. The method for preparing a silver-based highly reflective back electrode material according to claim 1, characterized in that: The particle size of the quaternary ammonium cationic polystyrene microspheres in step (2) is 100-200 nm.
7. The method for preparing a silver-based high-reflectivity back electrode material according to claim 1, characterized in that: The concentration of the quaternary ammonium cationic polystyrene microsphere aqueous solution in step (2) is 0.8-1.5 mg / mL.
8. The method for preparing a silver-based high-reflectivity back electrode material according to claim 1, characterized in that: The working conditions of the plasma device in step (3) are: the discharge voltage of the plasma power supply is 22 kV and the discharge frequency is 13 kHz.
9. The method for preparing a silver-based high-reflectivity back electrode material according to claim 1, characterized in that: The concentration of the silver nitrate aqueous solution in step (3) is 10-100 mM.
10. A method for preparing a silver-based high-reflectivity back electrode material according to claims 1 to 9, characterized in that: The silver-based high-reflectivity back electrode material is used in a high-power LED bottom packaging structure.